Evolution of the fish heart by sub/neofunctionalization of an elastin gene - Yuuta Moriyama (Nature Portfolio, 2016)
The bulbus arteriosus is an organ unique to the heart of teleosts, composed of specialized smooth muscle. Here, the authors show that the gene elastin b, which regulates cell fate of cardiac precursor cells into smooth muscle, evolved after whole-genome duplication and neofunctionalization in teleosts.